A techno-psychological approach to understanding problematic use of short-form video applications: The role of flow - Huang, Qing; Hu, Mingxin; Zhang, Ning (Frontiers in Psychology, 2022)
Short-form video applications (SVAs) have been gaining increasing popularity among users, which has raised the concern of problematic SVA use. Flow—a positive experience in which individuals feel immersion, enjoyment, temporal dissociation, and curiosity—contributes to the development of problematic SVA use. Most of the prior research examined the motivations of flow and the self-traits that trigger flow, but paid limited attention to the technological affordances of smartphone applications that facilitate users’ flow. Algorithm recommendation, multimodality, and low-cost interaction are three affordances of SVAs. Thus, drawing upon the stimulus-organism-response (S-O-R) framework, this study proposes a mediation model to examine how these affordances influence problematic SVA use through flow. An online survey (N = 621) showed that algorithm recommendation was negatively associated with problematic SVA use but was not significantly correlated to flow. Multimodality was directly and positively associated with problematic SVA use. Meanwhile, the relationship between these two variables were mediated by flow. Low-cost interaction had an indirect link with problematic SVA use via flow, while the direct link between them was not significant. The results suggest that low-cost interaction is the affordance that is most likely to trigger flow and problematic SVA use, followed by multimodality. However, algorithm recommendation seems to be an affordance that is less likely to facilitate flow or cause problematic SVA use. Our proposed model not only enriches the S-O-R framework in the digital environment, but also denotes a techno-psychological approach to examine problematic use of SVAs and other digital applications. Moreover, the findings offer practical implications for optimizing SVAs’ technological affordances to properly manage problematic SVA use.